Empowering Gen-Z: Pelatihan Digital Marketing Berbasis AI untuk Siswa SMK Nurul Jadid Paiton Probolinggo - Sudriyanto Sudriyanto; Kamil Malik; Jamal Jamal (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of digital technology requires the younger generation, especially vocational high school students, to have skills in digital-based marketing. However, many students still do not understand and master effective digital marketing strategies, especially those that utilize artificial intelligence (AI). Therefore, this community service activity aims to improve the understanding and skills of SMK Nurul Jadid Paiton Probolinggo students in AI-based digital marketing. The training was carried out through lecture methods, interactive discussions, and direct practice using various AI tools for digital marketing. Evaluation was carried out through pre-tests and post-tests to measure the effectiveness of the training. The results of the implementation showed a significant increase in student understanding and skills. The average pre-test score of 62.3 increased to 85.7 in the post-test, indicating the effectiveness of the practice-based learning approach. In addition, students were able to implement digital marketing strategies independently in business simulation projects. This activity not only provides short-term benefits but also contributes to students' readiness to face competition in the digital industry. As a follow-up, further mentoring and integration of materials into the school curriculum are recommended to ensure the sustainability of the benefits of this program.